2019
DOI: 10.1136/annrheumdis-2019-215571
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive serum interferon-α quantification during SLE remission identifies patients at risk for relapse

Abstract: ObjectivesMaintenance of remission has become central in the management of systemic lupus erythematosus (SLE). The importance of interferon-alpha (IFN-α) in the pathogenesis of SLE notwithstanding, its expression in remission has been poorly studied as yet. To study its expression in remission and its prognostic value in the prediction of a disease relapse, serum IFN-α levels were determined using an ultrasensitive single-molecule array digital immunoassay which enables the measurement of cytokines at physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 70 publications
3
54
1
2
Order By: Relevance
“…Despite the lack of correlation between the IFN signature and disease activity in some previous studies, we previously showed that patients with high levels of IFNinduced gene expression were more likely to have had a recent flare of their disease and had a higher rate of subsequent flare [6]. These observations, together with a recent report showing that SLE patients in remission with high serum IFN-α levels, as measured by an ultrasensitive technique (single molecule array assay), have a higher rate of subsequent flare than those with normal levels [11], led us to hypothesize that the IFN signature might be a biomarker of overall disease severity and that the correlation between this signature and disease activity in cross-sectional studies is due to these patients spending more of their time in an active disease state. In this study, we addressed this question through examination of the correlation between baseline IFN signature with disease activity and treatment over the subsequent 5 years.…”
Section: Introductionmentioning
confidence: 72%
“…Despite the lack of correlation between the IFN signature and disease activity in some previous studies, we previously showed that patients with high levels of IFNinduced gene expression were more likely to have had a recent flare of their disease and had a higher rate of subsequent flare [6]. These observations, together with a recent report showing that SLE patients in remission with high serum IFN-α levels, as measured by an ultrasensitive technique (single molecule array assay), have a higher rate of subsequent flare than those with normal levels [11], led us to hypothesize that the IFN signature might be a biomarker of overall disease severity and that the correlation between this signature and disease activity in cross-sectional studies is due to these patients spending more of their time in an active disease state. In this study, we addressed this question through examination of the correlation between baseline IFN signature with disease activity and treatment over the subsequent 5 years.…”
Section: Introductionmentioning
confidence: 72%
“…b 3D cluster representation (each sphere represents a patient; Dim3 reports minor difference in the third dimension, accentuated by SLEDAI-2K) to the typical "autoimmune" SLE, which is marked by an inverse correlation between complement and anti-dsDNA titre, supporting the interpretation that they behave as a different subset compared to hypocomplementemic SLE. These findings may look inconsistent with data from adult-onset SLE, showing a direct correlation between lupus activity and elevated IFNα [46]. The apparent difference may be due to distinct reasons: firstly, the dosage of serum IFNα is very challenging and results were not confirmed by analysis of ISGs expression [47]; secondly, the subgroup of subjects with normal complement levels and higher IFN inflammation could be more typical and easier to detect among cSLE compared with adult-SLE.…”
Section: Discussionmentioning
confidence: 69%
“…OLRs are intractable in ammatory diseases mainly caused by immune de ciency or dysregulation of oral immune system [20]. Cytokines are reliable biomarker for monitor the severity of in ammatory diseases [21,22]. In this study, unlike many previous studies on cytokine pro les from PBMCs between diseased and healthy subjects, we detected cytokine concentrations of intralesional and peripheral plasma from the participants, aiming at providing a more regional immune pro les of OLRs and revealing a reliable biomarker for monitoring the severity of OLRs on the molecular level.…”
Section: Discussionmentioning
confidence: 99%